Laryngeal Saccular Cyst. Issue 2 (2000) - Benoit, Craig; Day, Terry
Abstract : We present a case report of a 66-year-old female with a laryngeal saccular cyst that was treated endoscopically. Although this is an uncommon laryngeal anomaly, when it is recognized and managed appropriately early in the course of its presentation patient complications and morbidity can be avoided. The laryngeal saccular cyst can mimic or be associated with other, more serious, laryngeal pathology, including carcinoma of the larynx. Because of the known association between carcinoma of the larynx and laryngeal saccular cysts, these lesions should be fully evaluated endoscopically and surgically excised. Direct microlaryngoscopy with the use of the operating microscope is a safe and effective method for the treatment of laryngeal saccular cysts.